Questionnaire to Measure the Participation of Nursing Professionals in Mentoring Students - Agueda Cervera-Gasch; Loreto Macia-Soler; Blanca Torres-Manrique; Desirée Mena-Tudela; Pablo Salas-Medina; María Isabel Orts-Cortes; Víctor M González-Chordá (Universidad de Antioquia, 2017)
Objective. The aim herein was to validate a questionnaire to measure the level of participation of clinical nursing professionals in the mentorship of nursing students during clinical practices. Methods. Design and validation of a questionnaire. The psychometric properties of the tool were determined through four phases: 1- literature review; 2- evaluation of content validity; 3- pilot test, cognitive pretest and intra-observer reliability study; 4- construct validity study through an exploratory factor analysis of main components with varimax rotation in a sample of 249 nursing professionals from primary care and hospital care from different Spanish provinces. The internal consistency was studied with Cronbach's alpha coefficient. Results. The global content validity was above 0.8. The final version of the questionnaire had 33 items, with a global intraclass correlation coefficient of 0.852 and Cronbach's alpha of 0.837. Factor analysis explained 55.4% of the total variance, with a solution of five factors that made up the dimensions: Implication, Motivation, Satisfaction, Obstacles, and Commitment. Conclusion. The questionnaire evaluated has adequate validity and reliability to permit determining the level of nurse participation in the mentorship of students.   How to cite this article: Cervera-Gasch A, Macia-Soler L, Torres-Manrique B, Mena-Tudela D, Salas-Medina P, Orts-Cortes MI, et al. Questionnaire to Measure the Participation of Nursing Professionals in Mentoring Students. Invest. Educ. Enferm. 2017; 35(2):182-190.